Whole genome microarray analysis of growth hormone-induced gene expression in bone: T-box3, a novel transcription factor, regulates osteoblast proliferation - Govoni, Kristen E. (2006)
Growth hormone (GH) is important in the development and maintenance of bone; however, the IGF-dependent and -independent molecular pathways involved remain to be established. We used microarray analysis to evaluate GH signaling pathways in 4-wk-old GH-deficient mice following a single injection of GH (4 mg/kg body wt) or PBS (n = 6/group) at 6 or 24 h after treatment. Six thousand one hundred sixty genes were differentially expressed at P ≤ 0.05, and 17% of these genes were identified at both time points. Several of the genes differentially expressed were expressed sequence tags, and the remaining genes fell into 49 Gene Ontology categories. For subsequent studies, we focused on T-box (Tbx)3, a novel transcription factor, which increased more than twofold at both time points. Real-time RT-PCR analysis determined that pretreatment with IGF-binding protein-4 did not block GH-induced Tbx3 expression in vitro. Pretreatment with TNF-α blocked GH-induced Tbx3 expression. Tbx3 expression increased during osteoblast differentiation and following BMP-7 and Wnt3a treatment (P ≤ 0.05). Blocking Tbx3 expression by small interfering RNA decreased cell number and [(3)H]Thymidine incorporation (P < 0.01). In conclusion, 1) GH caused acute changes in several novel genes, suggesting that many GH-induced signaling pathways and target genes remain to be discovered; 2) because Tbx3 expression is regulated in osteoblasts and blockage of Tbx3 expression decreased cell number and DNA synthesis, we propose that Tbx3 is an important determinant of osteoblast cell number.